Improved reporting of overuse injuries and health problems in sport: an update of the Oslo Sport Trauma Research Center questionnaires - Clarsen, B.; Bahr, R.; Myklebust, G.; Andersson, S. H.; Docking, S. I.; Drew, M.; Finch, C. F.; Fortington, L. V.; Harøy, J.; Khan, K. M.; Moreau, B.; Moore, I. S.; et al. (British Journal of Sports Medicine, 2020)
In 2013, the Oslo Sports Trauma Research Center Overuse Injury Questionnaire (OSTRC-O) was developed to record the magnitude, symptoms and consequences of overuse injuries in sport. Shortly afterwards, a modified version of the OSTRC-O was developed to capture all types of injuries and illnesses-The Oslo Sports Trauma Research Center Questionnaire on Health Problems (OSTRC-H). Since then, users from a range of research and clinical environments have identified areas in which these questionnaires may be improved. Therefore, the structure and content of the questionnaires was reviewed by an international panel consisting of the original developers, other user groups and experts in sports epidemiology and applied statistical methodology. Following a review panel meeting in October 2017, several changes were made to the questionnaires, including minor wording alterations, changes to the content of one question and the addition of questionnaire logic. In this paper, we present the updated versions of the questionnaires (OSTRC-O2 and OSTRC-H2), assess the likely impact of the updates on future data collection and discuss practical issues related to application of the questionnaires. We believe this update will improve respondent adherence and improve the quality of collected data.